Involvement of a pertussis toxin-sensitive G-protein in the pharmacological properties of septo-hippocampal neurones. - Rascol, O. (1989)
1. The physiological and pharmacological properties of identified septo-hippocampal neurones (SHNs) have been studied in rats pretreated with the bacterial toxin, pertussis toxin (PTX). 2. In rats anaesthetized with urethane and pretreated with PTX, the axonal conduction velocity was unchanged while the mean spontaneous activity was significantly increased. 3. PTX pretreatment had no effect on responses of SHNs to the iontophoretic application of gamma-aminobutyric acid (GABA) and cholinoceptor agonists (acetylcholine or carbachol). 4. Baclofen and 5-hydroxytryptamine (5-HT), almost exclusively inhibitory in control rats, had little effect or an excitatory effect in PTX pretreated rats. 5. These results suggest the involvement of a pertussis toxin-sensitive G-protein in responses medicated by 5-HT and GABAB-receptors but not in responses mediated by cholinoceptors and GABAA-receptors in medial septum neurones projecting into the hippocampus.